Polyfluorinated Chemicals and Transformation Products - Knepper, Thomas P.; Lange, Frank T.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Due to their unparalleled effectiveness and efficiency, polyfluorinated chemicals (PFC) have become essential in numerous technical applications. However, many PFCs brought to market show limited biodegradability, and their environmental persistence combined with toxic and bioaccumulative potential have become a matter of concern in some instances. This volume highlights the synthesis of PFCs, focusing on substances with improved application and environmental properties, which are a challenge for synthetic chemists. Further, modern mass spectrometric techniques for the detection and identification of biotransformation products of PFCs are described. The sorption and leaching behavior of PFC in soil is also addressed in order to predict their fate in the environment. Several contributions discuss the monitoring of PFCs in European surface, ground and drinking waters, treatment options for PFC removal from drinking water, occurrence in food, and the human biomonitoring of PFCs.
Chemistry, Properties and Uses of Commercial Fluorinated Surfactants -- Perfluorinated Compounds – Occurrence and Uses in Products -- Mass Spectrometric Approaches to Reveal Biotransformation Products from Per- and Polyfluorinated Chemicals -- Sorption and Leaching Behavior of Perfluorinated Compounds in Soil -- Polyfluorinated chemicals in European Surface Waters, Ground- and Drinking Waters -- Treatment Options for the Removal and Degradation of Polyfluorinated Chemicals -- Perfluorinated Compounds in Food -- Human Biomonitoring of Perfluorinated Compounds.
Keywords: Environmental chemistry; Analytical chemistry; Environmental monitoring; Ecotoxicology; Geochemistry; Environmental health; Environmental Chemistry; Analytical Chemistry; Monitoring/Environmental Analysis; Ecotoxicology; Geochemistry; Environmental Health